2020
DOI: 10.3390/computers9010012
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adaptive Data Processing to Improve SLOs for Dynamic IoT Workloads

Abstract: Internet of Things (IoT) covers scenarios of cyber-physical interaction of smart devices with humans and the environment and, such as applications in smart city, smart manufacturing, predictive maintenance, and smart home. Traditional scenarios are quite static in the sense that the amount of supported end nodes, as well as the frequency and volume of observations transmitted, does not change much over time. The paper addresses the challenge of adapting the capacity of the data processing part of IoT pipeline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With the proliferation of microservices architecture, performance SLAs became even more challenging. In the context of event driven microservices architectures there has been some effort to autoscale event driven microservices communicating over a distributed event queue [11][12]. To our knowledge, none of the published work considers autoscaling event driven microservices in face of skewed workloads where a loadaware assignment of event queue partitions to consumers must be performed.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…With the proliferation of microservices architecture, performance SLAs became even more challenging. In the context of event driven microservices architectures there has been some effort to autoscale event driven microservices communicating over a distributed event queue [11][12]. To our knowledge, none of the published work considers autoscaling event driven microservices in face of skewed workloads where a loadaware assignment of event queue partitions to consumers must be performed.…”
Section: Related Workmentioning
confidence: 99%
“…In this set of experiments, we used the same workload employed in the research work of [11] as shown in Figure 6. To introduce skewness in the workload, for each batch of events in the workload, we sent 27% of events to P0 and 27% to P1, while we sent the 46% remaining events uniformly to P2, P3, P4.…”
Section: Binpack Autoscaling With a Second Skewed Workload And The Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper Self-Adaptive Data Processing to Improve SLOs for Dynamic IoT Workloads [20] by Chindanonda, Podolskiy, and Gerndt addresses the challenge of adapting the capacity of the data processing part of IoT pipeline in response to dynamic workloads for centralized IoT scenarios where the quality of user experience matters, e.g., interactivity and media streaming as well as the predictive maintenance for multiple moving vehicles, centralized analytics for wearable devices and smartphones. In their paper, the authors propose augmentations to the computation schemes of data processing component's desired replicas count from the previous work; these augmentations aim to repurpose original sets of metrics to tackle the task of SLO violations minimization for dynamic workloads instead of minimizing the cost of deployment in terms of instance seconds.…”
Section: Contributions To This Special Issuementioning
confidence: 99%